Analisis Kesulitan Guru dalam Melaksanakan Penilaian Autentik pada Kurikulum 2013 di SDN 104208 Cinta Rakyat - Grace Theo Fanny Lumbanbatu; Faiza Arsila; Lince Marwiyah Tanjung; Putri Sadaria Simangunsong; Laurensia M. Perangin-Angin (Publikasi Indonesia, 2022)
Along with the implementation of the 2013 curriculum, many changes occurred in the learning components, especially in the assessment system, which in the 2013 curriculum is known as authentic assessment. Authentic assessment emphasizes activity-based learning that covers aspects of attitude, cognitive and psychomotor. The implementation of authentic assessments in the field is still not running as it should. There are still many teachers who have difficulty in carrying out authentic assessments in schools due to several factors. This study aims to describe the difficulties of teachers in carrying out authentic assessments in the 2013 curriculum at SD Negeri 104208 Cinta Rakyat. Data collection techniques were carried out through interviews and documentation. The sample in this research is a VB grade teacher at SD Negeri 104208 Cinta Rakyat. The data analysis technique uses interactive model data analysis techniques. Based on the results of data analysis, the results of the study show that there are several difficulties experienced by teachers in carrying out authentic assessments in the 2013 curriculum including (1) Incompatibility of the assessment rubrics in the teacher's book with current learning (2) Lack of improvisation in using assessment instruments ( 3) The problem of time constraints. The teacher's efforts/solutions to overcome the difficulties of authentic assessment are; (1) the teacher continues to carry out all the assessments in the teacher's book which includes the attitude domain, cognitive domain and pricomotor domain, (2) the teacher conducts discussions with fellow teachers at the school and the teacher practices to vary the existing attitude assessment, (3) teachers practice to pay more attention to how to manage time well so that the implementation of the assessment can be more optimal by dividing the days in conducting this authentic assessment.